Dynamic Capability Moderated Influence Financial Literacy On Performance Small And Medium Enterprises - Ita Juwita (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study aims to analyze the influence of dynamic capability and financial literacy on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Kendari City, as well as examine the role of financial access in explaining and strengthening the relationship between variables in the model. The research uses a quantitative approach with objective numerical data processing. Data were collected through a closed-ended questionnaire compiled based on indicators in the previous literature, then measured using a five-point Likert scale from strongly disagree to strongly agree. The research respondents are MSME actors in Kendari City who have been running a business for at least two years, with a sample of 190 respondents, so as to be able to describe the empirical conditions of business actors who have operational experience. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares because it was able to test conceptual models that involve direct influence and moderation testing simultaneously and more flexibly on the characteristics of data distribution. Data processing using SmartPLS includes evaluation of measurement models through validity and reliability tests as well as structural model testing. The results of the study show that dynamic capability has a positive and significant effect on the performance of MSMEs. Financial literacy also has a significant effect on performance and has a very strong influence on financial access, so financial literacy is an important factor that encourages the connection of MSMEs with financial services. Financial access has been proven to have a significant effect on performance and strengthen the influence of dynamic capability on performance, so that the adaptive ability of business actors will produce more optimal performance when supported by adequate access to financing and financial services. These findings emphasize the need for a strategy to strengthen business adaptability that is integrated with increasing literacy and financial access to encourage the performance of MSMEs in a sustainable manner.